The Long and Winding Road to Personalized Glycemic Control in the Intensive Care Unit - Tickoo, Mayanka (Seminars in Respiratory and Critical Care Medicine, 2019)
In the critically ill adult, dysglycemia is a marker of disease severity and is associated with worse clinical outcomes. Close monitoring of glucose and use of insulin in critically ill patients have been done for more than 2 decades, but the appropriate target glycemic range in critically ill patients remains controversial. Physiological stress response, levels of inflammatory cytokines, nutritional intake, and level of mobility affect glycemic control, and a more personalized approach to patients with dysglycemia is warranted in critically ill intensive care unit (ICU) patients. We discuss the pathophysiology and downstream effects of altered glycemic response in critical illness, management of glycemic control in the ICU, and future strategies toward personalization of critical care glycemic management.
Keywords: hyperglycemia; hypoglycemia; glycemic variability; critical illness; insulin